Pointwise Reconstruction of Interferometric Phase - Barseghyan, Yuri (Mathematical Problems of Computer Science, 2021)
In this work the problem of interferometric phase reconstruction is considered. The pointwise approximation approach is proposed, which provides stable results even for bad quality of interferogramms. Experimental results show that the developed algorithm demonstrates better performance in comparison with some of the state-of-the- art techniques.